Preparation method and application of ammonium ion pre-embedded Cu-MOF-derived CuHCF / MXene electrode material

By pre-embedding ammonium ions in CuHCF and self-assembly with MXene, the problems of easy agglomeration and poor conductivity of CuHCF and MXene electrode materials are solved, the adsorption capacity of NH4+ and the conductivity of electrode materials are improved, and efficient NH4+ removal and resources are achieved Recycling meets the needs of capacitor deionization technology.

CN119285047AActive Publication Date: 2025-01-10SICHUAN AGRI UNIV

Patent Information

Application Number
CN202411403236.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

In the existing capacitive deionization technology, CuHCF and MXene electrode materials are prone to agglomeration and poor conductivity, resulting in poor NH4+ removal performance, which is difficult to meet market application requirements.

Method used

By pre-embedding ammonium ions in CuHCF and self-assembly with MXene, an ammonium ions are pre-embedded CuHCF/MXene electrode material derived from Cu-MOF is formed, and the NH4+ adsorption potential energy is increased by hydrogen bonding, and CuHCF agglomeration is prevented through the large layer spacing of MXene, improving conductivity sex.

Benefits of technology

It significantly improves the adsorption capacity of NH4+ and the conductivity of electrode materials, achieves efficient NH4+ removal and resource recovery, and has a simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285047A_ABST
    Figure CN119285047A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an ammonium ion pre-embedded Cu-MOF derived CuHCF / MXene electrode material, and relates to the technical field of new energy nanometer materials. According to the preparation method, Cu-BTC is taken as a sacrificial template, ammonium ion pre-embedding and flaky MXene compounding are carried out, and synthesis is carried out under the condition of coprecipitation at room temperature. The preparation method provided by the invention is low in cost and simple in process, and the obtained electrode material is excellent in morphology and performance. When the prepared CuHCF / MXene composite electrode is applied to capacitive deionization, the characteristic of high NH4 < + > adsorption capacity is shown. According to the preparation method, hydrogen-bond interaction is formed between H atoms in NH4 < + > and N atoms in CuHCF, so that the NH4 < + > adsorption potential energy is reduced, the adsorption capacity is improved, and meanwhile, the defects that CuHCF is prone to agglomeration, poor in conductivity and the like are overcome through self-assembly of the CuHCF and MXene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy nanomaterials, and in particular to a preparation method and application of a CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF. Background Art

[0002] With the development of industry and the growth of population, a large amount of ammonia (NH4 + ) Through the discharge of sewage into cities, it causes eutrophication of water bodies and greenhouse gas emissions, which may seriously endanger the health of aquatic ecological environment. Effectively remove NH4 in wastewater + It is a difficult problem that needs to be solved urgently. In recent years, capacitive deionization (CDI) wastewater treatment technology has attracted much attention due to its advantages such as low energy consumption, environmental friendliness and renewable electrode materials.

[0003] Capacitive deionization electrodes are composed of electrode active materials, binders, conductive agents and graphite current collectors, among which the electrode active materials are the key factors determining the performance of capacitive deionization. At present, carbon materials, metal oxides and metal sulfides have been reported as electrode materials in the field of capacitive deionization. Although the above electrode materials can greatly improve their ability to purify NH4 + However, due to the limitation of its intrinsic properties, it is still difficult to meet the requirements of market applications. Prussian blue analogs (such as CuHCF) as typical intercalation materials have stable three-dimensional framework structure and large ion diffusion channels, and two-dimensional materials MXene have large interlayer vacancies and high conductivity, which can be used as the main material for rapid insertion / deinsertion of cations in CDI. However, CuHCF prepared by traditional coprecipitation method is mostly in large blocks and easy to agglomerate. This leads to NH4 + Defects such as difficulty in embedding, ion diffusion and slow reaction kinetics have seriously affected the NH4 + In addition, due to the van der Waals force, MXene nanosheets easily stack themselves and produce irreversible agglomeration, resulting in a serious reduction in exposed active sites and deterioration of various excellent properties. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a preparation method and application of CuHCF / MXene electrode materials derived from Cu-MOF pre-embedded with ammonium ions, by NH4 + The H atoms in CuHCF form hydrogen bonds with the N atoms in CuHCF, making it possible to + The adsorption potential energy is reduced, thereby improving the adsorption capacity. At the same time, the defects of CuHCF such as easy agglomeration and poor conductivity are improved through its self-assembly with MXene.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF is provided, comprising the following steps:

[0006] (1) dissolving copper nitrate hexahydrate in deionized water to obtain solution A; dissolving trimesic acid in ethanol to obtain solution B; then adding polyvinyl pyrrolidone to solution B, and then pouring the solution into solution A under stirring conditions, transferring the solution into a high-pressure reactor, performing hydrothermal reaction, centrifugation washing and vacuum drying to obtain a template Cu-BTC;

[0007] (2) adding the template Cu-BTC obtained in step (1) to an ethanol solution, and sonicating to obtain solution C; adding potassium ferrocyanide to deionized water to obtain solution D; then adding the flaky MXene solution to solution D under stirring conditions, and stirring; then adding solution C under stirring conditions to react; finally, adding ammonium chloride, stirring, and reacting at room temperature; after washing and vacuum drying, obtaining a CuHCF / MXene electrode material derived from Cu-MOF pre-embedded with ammonium ions.

[0008] Furthermore, in step (1), the molar mass ratio of copper nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone is 2-5 mmol: 2-3 mmol: 0.1-0.3 g.

[0009] Furthermore, in step (1), the molar mass ratio of copper nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone is 3.6 mmol:2 mmol:0.1 g.

[0010] Furthermore, in step (1), in solution A, the molar volume ratio of copper nitrate hexahydrate to deionized water is 2-5 mmol:15 mL; and in solution B, the molar volume ratio of trimesic acid to ethanol is 2-3 mmol:15 mL.

[0011] Furthermore, in step (1), the hydrothermal reaction is carried out at a temperature of 110-130° C. for 10 h.

[0012] Furthermore, in step (1), ethanol is centrifuged for washing and vacuum dried at 60° C. for 24 h.

[0013] Furthermore, in step (1), copper nitrate hexahydrate may be replaced by nickel nitrate hexahydrate.

[0014] Furthermore, in step (2), the molar mass ratio of the template Cu-BTC, potassium ferrocyanide, sheet-like MXene and ammonium chloride is 60-90 mg: 0.3-0.5 mmol: 10-20 mg: 60-80 mg.

[0015] Furthermore, in step (2), in solution C, the mass volume ratio of template Cu-BTC and ethanol solution is 60-90 mg:15 mL; in solution D, the molar volume ratio of potassium ferrocyanide and deionized water is 0.3-0.5 mmol:15 mL; and the concentration of flaky MXene solution is 5-8 mg / mL.

[0016] Furthermore, the concentration of the flake MXene solution was 6 mg / mL.

[0017] Furthermore, in solution D, the molar volume ratio of potassium ferrocyanide to deionized water is 0.3 mmol:15 mL.

[0018] Furthermore, in step (2), solution C is added under stirring at 20-25° C. and reacted for 12 h.

[0019] Furthermore, in step (2), ammonium chloride is added, stirred for 10 min, and then reacted at room temperature for 12 h.

[0020] Furthermore, the sample was washed with ethanol three times and dried under vacuum at 60°C for 10 h.

[0021] The present invention also provides a CuHCF / MXene electrode material derived from ammonium ions pre-embedded in Cu-MOF, obtained by the preparation method of the CuHCF / MXene electrode material derived from ammonium ions pre-embedded in Cu-MOF.

[0022] The present invention also provides the use of the above-mentioned ammonium ion pre-embedded Cu-MOF-derived CuHCF / MXene electrode material in capacitor deammonium ion removal.

[0023] The present invention has the following beneficial effects:

[0024] 1. The ammonium ion pre-embedded CuHCF / MXene electrode prepared by the present invention can not only improve its NH4 + The adsorption potential can also reduce NH4 + At the same time, the large interlayer spacing of MXene can prevent the agglomeration of CuHCF particles and improve its poor conductivity. This composite structure is conducive to improving the electrode material's NH4 + effective adsorption capacity.

[0025] 2. The ammonium ion pre-embedded CuHCF / MXene electrode prepared in the present invention is used as the cathode material of the CDI device, which helps to achieve efficient NH4 + Resource recycling is an electrode material with great commercial value. The preparation method of ammonium ion pre-embedded CuHCF / MXene electrode provided by the present invention effectively overcomes the disadvantages of complex preparation process and poor repeatability.

[0026] 3. The present invention can control the grain size of CuHCF derived from Cu-BTC, and due to NH4 + The formation of hydrogen bonds between the H atoms in CuHCF and the N atoms in CuHCF is more conducive to obtaining excellent kinetic performance. The technical route designed in the present invention to synthesize ammonium ions pre-embedded in CuHCF / MXene composites using Cu-BTC as a sacrificial template fully combines the dual pseudocapacitance and synergistic reaction of CuHCF and MXene to jointly promote the ion reaction kinetics, thereby improving its NH4 + adsorption performance.

[0027] 4. The present invention uses Cu-BTC as a sacrificial template, and after pre-embedding of ammonium ions and compounding with sheet MXene, it is synthesized under room temperature coprecipitation conditions. The preparation method proposed in the present invention has low cost and simple process, and the obtained electrode material has excellent morphology and performance. The prepared CuHCF / MXene composite electrode is applied to capacitor deionization, showing high NH4 + Adsorption capacity characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD pattern of the material obtained in Example 1;

[0029] Figure 2 This is the SEM image of the material obtained in Example 1;

[0030] Figure 3 This is a constant current discharge curve diagram of the material obtained in Example 1;

[0031] Figure 4 NH4 of the material obtained in Example 1 + Desalination capacity diagram. DETAILED DESCRIPTION

[0032] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0033] Example 1

[0034] A CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF, the preparation method of which comprises the following steps:

[0035] (1) 3.6 mmol of copper nitrate hexahydrate was dissolved in 15 mL of deionized water to obtain solution A; 2 mmol of trimesic acid was dissolved in 15 mL of ethanol to obtain solution B, and then 0.1 g of polyvinyl pyrrolidone was added to solution B, and then poured into solution A under stirring conditions, and transferred to a high-pressure reactor, and hydrothermally reacted at 120° C. for 10 h, and then washed by centrifugation with ethanol, and vacuum dried at 60° C. for 24 h to obtain a template Cu-BTC;

[0036] (2) 60 mg of the template Cu-BTC obtained in step (1) was added to 15 mL of ethanol solution and ultrasonicated for 90 min to obtain solution C; 0.3 mmol of potassium ferrocyanide was added to 15 mL of deionized water to obtain solution D, and then 10 mg of 6 mg / mL flake MXene solution was slowly added to solution D under stirring conditions and stirred for 10 min, and then solution C was slowly added under stirring conditions and reacted at 20°C for 12 h. Finally, 60 mg of ammonium chloride was added and stirred for 10 min, and then reacted at room temperature for 12 h, washed with ethanol three times, and vacuum dried at 60°C for 10 h to obtain ammonium ion pre-embedded Cu-MOF-derived CuHCF / MXene electrode material.

[0037] Example 2

[0038] A CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF, the preparation method of which comprises the following steps:

[0039] (1) 3.6 mmol of copper nitrate hexahydrate was dissolved in 15 mL of deionized water to obtain solution A; 2 mmol of trimesic acid was dissolved in 15 mL of ethanol to obtain solution B, and then 0.1 g of polyvinyl pyrrolidone was added to solution B, and then poured into solution A under stirring conditions, and transferred to a high-pressure reactor, and hydrothermally reacted at 120° C. for 10 h, and then washed by centrifugation with ethanol, and vacuum dried at 60° C. for 24 h to obtain a template Cu-BTC;

[0040] (2) 90 mg of the template Cu-BTC obtained in step (1) was added to 15 mL of ethanol solution and ultrasonicated for 90 min to obtain solution C; 0.3 mmol of potassium ferrocyanide was added to 15 mL of deionized water to obtain solution D, and then 20 mg of 6 mg / mL flake MXene solution was slowly added to solution D under stirring conditions and stirred for 10 min, and then solution C was slowly added under stirring conditions and reacted at 20°C for 12 h. Finally, 80 mg of ammonium chloride was added and stirred for 10 min, and then reacted at room temperature for 12 h, washed with ethanol three times, and vacuum dried at 60°C for 10 h to obtain ammonium ion pre-embedded Cu-MOF derived CuHCF / MXene electrode material.

[0041] Example 3

[0042] A NiHCF / MXene electrode material derived from Ni-MOF pre-embedded with ammonium ions, the preparation method of which comprises the following steps:

[0043] (1) 3.6 mmol of nickel nitrate hexahydrate was dissolved in 15 mL of deionized water to obtain solution A; 2 mmol of trimesic acid was dissolved in 15 mL of ethanol to obtain solution B, and then 0.1 g of polyvinyl pyrrolidone was added to solution B, and then poured into solution A under stirring conditions, and transferred to a high-pressure reactor, and hydrothermally reacted at 120° C. for 10 h, and then washed by centrifugation with ethanol, and vacuum dried at 60° C. for 24 h to obtain a template Ni-BTC;

[0044] (2) 90 mg of the template Ni-BTC obtained in step (1) was added to 15 mL of ethanol solution and ultrasonicated for 90 min to obtain solution C; 0.5 mmol of potassium ferrocyanide was added to 15 mL of deionized water to obtain solution D, and then 20 mg of 6 mg / mL flake MXene solution was slowly added to solution D under stirring conditions and stirred for 10 min, and then solution C was slowly added under stirring conditions and reacted at 20°C for 12 h. Finally, 80 mg of ammonium chloride was added and stirred for 10 min, and then reacted at room temperature for 12 h, washed with ethanol three times, and vacuum dried at 60°C for 10 h to obtain ammonium ion pre-embedded Ni-MOF derived NiHCF / MXene electrode material.

[0045] The physical properties of the material obtained in Example 1 were characterized by X-ray diffractometer and scanning electron microscope. Figure 1 and Figure 2 The material obtained in Example 1 was subjected to electrochemical and capacitive deionization tests, and the results were shown in Figure 3 and 4 .

[0046] Depend on Figure 1 It can be seen that by comparing with the standard card, it can be determined that the material obtained in Example 1 is a composite of CuHCF and MXene.

[0047] Depend on Figure 2 It can be seen that MXene presents a nanosheet structure and CuHCF presents a particle structure. This composite structure is conducive to the transmission of electrolyte ions and interface electrons.

[0048] Depend on Figure 3 It can be seen that the specific capacitance is as high as 263.1 F / g at a current density of 0.2 A / g, indicating its good capacitive behavior.

[0049] Depend on Figure 4 It can be seen that in a short period of time, NH4 + The adsorption capacity reached a maximum of 38.9 mg / g, indicating that it has excellent electrical adsorption capacity.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a CuHCF / MXene electrode material derived from Cu-MOF pre-embedded with ammonium ions, characterized in that: The following steps are involved: (1) dissolving copper nitrate hexahydrate in deionized water to obtain solution A; dissolving trimesic acid in ethanol to obtain solution B; then adding polyvinyl pyrrolidone to solution B, and then pouring the solution into solution A under stirring conditions, transferring the solution into a high-pressure reactor, performing hydrothermal reaction, centrifugation washing and vacuum drying to obtain a template Cu-BTC; (2) adding the template Cu-BTC obtained in step (1) to an ethanol solution, and sonicating to obtain solution C; adding potassium ferrocyanide to deionized water to obtain solution D; then adding the flaky MXene solution to solution D under stirring conditions, and stirring; then adding solution C under stirring conditions to react; finally, adding ammonium chloride, stirring, and reacting at room temperature; after washing and vacuum drying, obtaining a CuHCF / MXene electrode material derived from Cu-MOF pre-embedded with ammonium ions.

2. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (1), the molar mass ratio of copper nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone is 2-5 mmol: 2-3 mmol: 0.1-0.3 g.

3. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (1), in solution A, the molar volume ratio of copper nitrate hexahydrate to deionized water is 2-5 mmol:15 mL; in solution B, the molar volume ratio of trimesic acid to ethanol is 2-3 mmol:15 mL.

4. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (1), the hydrothermal reaction is carried out at a temperature of 110-130° C. for 10 h.

5. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (2), the molar mass ratio of the template Cu-BTC, potassium ferrocyanide, sheet-like MXene and ammonium chloride is 60-90 mg: 0.3-0.5 mmol: 10-20 mg: 60-80 mg.

6. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (2), in solution C, the mass volume ratio of template Cu-BTC and ethanol solution is 60-90 mg:15 mL; in solution D, the molar volume ratio of potassium ferrocyanide and deionized water is 0.3-0.5 mmol:15 mL; and the concentration of flaky MXene solution is 5-8 mg / mL.

7. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (2), solution C is added under stirring at 20-25° C. and reacted for 12 h.

8. The method for preparing the CuHCF / MXene electrode material derived from ammonium ion pre-embedded Cu-MOF according to claim 1, characterized in that: In step (2), ammonium chloride was added, stirred for 10 min, and then reacted at room temperature for 12 h.

9. The ammonium ion pre-embedded Cu-MOF derived CuHCF / MXene electrode material obtained by the preparation method of the ammonium ion pre-embedded Cu-MOF derived CuHCF / MXene electrode material according to any one of claims 1 to 8.

10. Use of the ammonium ion pre-embedded Cu-MOF derived CuHCF / MXene electrode material according to claim 9 in capacitor deammonium ion removal.

Citation Information

Patent Citations

  • Prussian blue analog / MXene composite electrode material and in-situ preparation method and application thereof

    CN110783536A

  • Preparation method of membrane-free ammonium ion selective electrode based on Prussian blue derivative

    CN115015355A

  • Ammonium ion hybrid capacitor and preparation method of electrode material thereof

    CN116313567A

  • Preparation method and application of Prussian blue analogue electrode applied to hybrid capacitive deionization

    CN116959895A

  • Flexible ion actuator based on MXene / Ni-PBAs composite material and preparation method and application thereof

    CN117228794A

Cited By

  • Amino-modified MXene electrode and preparation method and application thereof

    CN121085373A

  • Copper ferrocyanide / copper benzenehexophenol electrode material as well as preparation method and application of copper ferrocyanide / copper benzenehexophenol electrode material

    CN121186153A

  • Composite electrode material for electrochemical desalination and preparation method and application thereof

    CN121494151A